Femininity and domination: studies in the phenomenology of oppression - Bartky, Sandra Lee (Routledge, 1990)
Bartky s'appuie sur l'expérience de la vie quotidienne pour démasquer les nombreux déguisements par lesquels les intimations d'infériorité sont infligées aux femmes. Elle critique à la fois le parti pris masculin de la théorie actuelle et la domination débilitante détenue par les notions de «féminité appropriée» sur les femmes et leurs corps dans la culture patriarcale.
Keywords: 1900-1999; amériques; approches et analyses; cours; cycles supérieurs; discipline; fem1000; fem7000; lit3220; patriarcat; phénoménologie; premier cycle; périodes historiques; régions géographiques; sciences humaines; systèmes d'oppressions; états-unis

II. Une perspective féministe dans l’histoire des congrégations de femmes - Dumont, Micheline (Études d'histoire religieuse, 1990)
Keywords: 1900-1999; 1960-1969; 1970-1979; amérique du nord; amériques; approches et analyses; canada; care; cours; discipline; discours dominant; his4550; histoire; patriarcat; premier cycle; périodes historiques; québec; religion; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; travail

Social Criticism without Philosophy: An Encounter between Feminism and Postmodernism - Fraser, Nancy; Nicholson, Linda J. (Feminism/postmodernism, 1990)
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; discipline; fem1000; philosophie; postmodernisme; premier cycle; périodes historiques; régions géographiques; sciences humaines; théories culturelles; états-unis

Homeplace : a site of resistance dans Yearning: race, gender, and cultural politics - Hooks, Bell (Yearning: race, gender, and cultural politics, 1990)
bell hooks crosses boundaries in major debates on postmodern theory, cultural criticism, and the politics of race and gender. She warns that “discourse” about “difference” is dangerously detachable from more essential struggles.
Section: 236 p
Keywords: 1900-1999; 1980-1989; afro-féminisme; amérique du nord; amériques; antiracisme; approches et analyses; cours; discipline; féminisme afroaméricain; histoire et politique; patriarcat; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; soc3113; sociologie; systèmes d'oppressions; thématiques; violences; états-unis

La formation professionnelle des filles dans les écoles supérieures de musique tenues par les religieuses (1926-1960) - Mendez, Manon (Université de Sherbrooke, 1990)
http://savoirs.usherbrooke.ca/handle/11143/1992
Keywords: 1900-1999; 1920-1929; 1930-1939; 1940-1949; 1950-1959; amériques; congrégations religieuses féminines; discipline; genre; histoire; histoire des femmes*; mémoires/thèses; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; école

Feminism/postmodernism - Nicholson, Linda J. (Routledge, 1990)
In this anthology, prominent contemporary theorists assess the benefits and dangers of postmodernism for feminist theory. The contributors examine the meaning of postmodernism both as a methodological position and a diagnosis of the times. They consider such issues as the nature of personal and social identity today, the political implications of recent aesthetic trends, and the consequences of changing work and family relations on women's lives. Contributors: Seyla Benhabib, Susan Bordo, Judith Butler, Christine Di Stefano, Jane Flax, Nancy Fraser, Donna Haraway, Sandra Harding, Nancy Hartsock, Andreas Huyssen, Linda J. Nicholson, Elspeth Probyn, Anna Yeatman, Iris Young.
Keywords: 1900-1999; 1980-1989; amériques; anthologie; approches et analyses; cours; discipline; fem1000; philosophie; postmodernisme; premier cycle; périodes historiques; régions géographiques; sciences humaines; théories culturelles; théories féministes; états-unis